Utilization of Information Resources and Students’ Academic Performance in Tertiary Institutions in Cross River State, Nigeria - EKPANG, Patience Owere; IDHALAMA, Ogagaoghene Uzezi (Researchparks Publishing, 2024)
This research aims to explore the utilization of information resources and its impact on the academic performance of students in tertiary institutions in Cross River State, Nigeria. The study will be conducted in the context of the increasing reliance on information and communication technologies (ICTs) in the education sector. The objectives of this research are: Examine the relationship between adequacy of information resources and students’ academic performance in tertiary institutions in Cross River State, examine the relationship between organization of information resources and students’ academic performance in tertiary institutions in Cross River State and examine the relationship between accessibility of information resources and students’ academic performance in tertiary institutions in Cross River State To achieve these objectives, a descriptive (quantitative) approach was employed. A survey was administered to a sample of students from various tertiary institutions in Cross River State. The survey gathered data on students' awareness and availability of information resources and their frequency of utilization for academic purposes. The data collected from the survey were analyzed using appropriate statistical techniques using descriptive statistics, such as frequencies and percentages, to determine the level of awareness, availability, and utilization of information resources. Correlation and regression analysis were employed to examine the relationship between the utilization of information resources and students' academic performance. The results of this study led to the conclusion that utilization of information resources has a strong, significant and positive relationship with students’ academic performance in tertiary institutions in Cross River State. Also, the independent variables: adequacy, organization and accessibility of information resources of the study shared a significant relationship with academic performance of students in tertiary institutions. Thus, for academic library (librarians) to continue to serve their essence in sustaining students’ academic performance, care must be taken to ensure that library resources are adequate, well organized and accessible to all students of the academic community. Based on the result of the study, the following recommendations were made: That tertiary institutions and academic libraries should set-up principles for evaluation of students’ level of utilization of information resources in order to ascertain to what extent library resources are utilized and do something about it and that academic librarians should periodically review library resources to check their level of adequacy, organization and accessibility so that their role would be significant in promoting effective utilization of information resources and academic performance of students in tertiary institutions.